Peranan Perempuan Desa Hutan Dalam Pembangunan Hutan Tanam Jati Di KPH Madiun - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2001)
The objective of this research is to study the role of forest village women including : I) the process of knowledge and experience transfer on the development of teak Ibrest to female workers